Molecular investigation of uniparental disomy (UPD) in spontaneous abortions. (May 2019) - Lalou, Iliana; Gkrozou, Fani; Meridis, Eleftherios; Tsonis, Orestis; Paschopoulos, Minas; Syrrou, Marika
Abstract: Objective: About 10–15% of all clinically recognized pregnancies end as spontaneous abortions while at least 50% of pregnancies are lost before reaching term gestation. Genetic abnormalities are responsible for ≥50% of all early miscarriages. The aim is to indentify associations between UPD and abortions and regarding UPD as pathogenetic mechanism possibly to understand the role of imprinted genes or recessive mutations in abortions. Study design: To determine additional factors causing spontaneous abortions we searched for uniparental disomies (UPD) which is known to be associated with distinct birth defects as per the chromosome involved and parental origin. Studies were carried on DNA of 68 cases of first trimester spontaneous abortions and DNA of their parents. We examined tissue from aborted fetuses, especially in the first trimester, with molecular techniques to detect UPD to chromosomes that contain imprinting genes.The inheritance of each region of the chromosome was determined by comparing the genotypes obtained from abortion and parental DNA. Results: Of the 68 cases of spontaneous abortions investigated, 324% were found to be biparental inheritance or were uninformative in locus that they were examined, 4118% were matUPD, 147% trisomy for a chromosome, 8, 8% patUPD and 294% matUPD and trisomy for a certain chromosome. Most cases of UPD found on chromosomes 21 and 14. Many of those are found in combination with chromosomes 13, 20 and 22. Conclusions: UPD might be a common finding among spontaneous abortuses. UPD can be a cause of miscarriage if localized to regions of chromosomes with imprinted genes which control embryogenesis and fetal development and or can activate a recessive mutation in genes which are essential for early embryogenesis.